Comparative study of motor speed synchronization control for an integrated motor–transmission powertrain system. (March 2020) - Huang, Jianfeng; Zhang, Jianlong; Yin, Chengliang
This paper compares several kinds of methods for motor speed synchronization control, which plays an important role in gear shifting of emerging clutchless automated manual transmissions for battery electric vehicles and other powertrain systems for hybrid electric vehicles. Specifically, four controllers, namely, proportional-integral control, disturbance observer–based proportional control, integral sliding mode–based proportional control, and disturbance observer–based act-and-wait control, are compared in transient responses regarding settling time, overshoot, and steady-state error. Each is formulated by combining one nominal controller for speed tracking and another for disturbance compensation. For disturbance observer–based proportional control, model-based determination of the feedback gain and disturbance observer gain is discussed. Simulations and experiments are carried out to study effects of different controller parameter settings and evaluate performances of different methods under different operation conditions with disturbances and uncertainties like plant parameter drift, communication time delay, unknown load torques, and so on. Based on the results, it is advised that disturbance observer–based proportional control with the reference signal set as the nominal speed trajectory be used in practice, since it comes with merits of few controller parameters to be determined as well as robust, consistent, and satisfactory performances.